Remittances, institutions and economic growth - Natalia Catrinescu; Miguel Leon-Ledesma; Matloob Piracha; Bryce Quillin (Institute for the Study of Labor (IZA), 2006)
There is considerable debate regarding the relative contribution of international migrants' remittances to sustainable economic development. While the rates and levels of officially recorded remittances to developing countries has increased enormously over the last decade, academic and policy-oriented research has not come to a consensus over whether remittances contribute to longer-term growth by building human and financial capital or degrade long-run growth by creating labor substitution and 'Dutch disease' effects. This paper suggests that contradictory findings have emerged when looking at the remittances-growth link because previous studies have not correctly controlled for endogeneity. Using Dynamic Data Panel estimates we find that remittances exert a weakly positive impact on long-term macroeconomic growth. The paper also considers the proposition that the longer-term developmental impact of remittances is increased in the presence of sound economic policies and institutions.
Keywords: F22; O15; O47; 330; international migration; remittances; growth; institutions